Quantitative evaluation of root canal surface roughness after filing with adaptive reciprocating and continuous rotary instruments. Issue 6 (31st January 2017) - Sakhaei Manesh, Vahid; Giacomin, Paul; Stoll, Richard
Abstract: Obtaining clean and smooth root canal walls is the ideal clinical outcome of the cleaning and shaping stage in root canal treatment. This study compares the surface roughness of root canal surfaces instrumented with a NiTi filing system with either adaptive reciprocating (AR) or continuous rotation (CR). Root canal cleaning and shaping was carried out on the mesial canals of 24 extracted first molars roots with either AR or CR. Roots were split in half and the surface roughness of their canals was evaluated in 12 three dimensional roughness reconstructions using a scanning electron microscope. Rz (nm) values were calculated in three areas of each reconstruction and analyzed ( α  = 0.05). Mann‐Whitney tests showed that surface roughness was significantly higher overall in the AR group (Rz = 967 ± 250 nm) compared with the CR group (Rz = 739 ± 239 nm; p  = 0.044). The roughness values generally increased from apical towards the coronal third in both groups. A less aggressive finishing file or a continuous rotary system to end the cleaning and shaping stage may be beneficial to reduce roughness of the root canal surface. Abstract : This study compares the root canal surface roughness after instrumentation with different motions (continuous rotation or adaptive reciprocation). Continuous rotating files provided a final smoother surface compared to reciprocating instruments.